A self-catalytic carbon paste electrode for the detection of vitamin B12. - Tomcik, P; Banks, C; Davies, T; Compton, R (2004)
A simple, sensitive, and selective method for the detection of vitamin B12 (cyanocobalamin) is presented. A carbon paste electrode has been constructed with trans-1,2-dibromocyclohexane (DBCH) acting as both the paste binder and a reactive material facilitating the electrocatalytic detection of the target. The latter reaction is based on the electroreduction of the Co(III) center in vitamin B12 to Co(I), which specifically reacts with DBCH to produce electrocatalytic currents with the regeneration of Co (II); a detection limit of 8.5 x 10(-10) mol dm(-3) (based on 3sigma) was found. The electrode has been successfully used for the quantification of vitamin B12 in pharmaceutical products and biological matrix media.